Unpacking intersecting complexities for WASH in challenging contexts: A review. (1st February 2022) - Rhodes-Dicker, Leandra; Brown, Nick J.; Currell, Matthew
Highlights: Complexities intersect to affect access to water, sanitation, and hygiene (WASH). Challenging contexts are lagging in access to WASH and require targeted approaches. Failure to understand intersecting complexities has led to inappropriate solutions. A practical approach is needed to unpack context-specific intersecting complexities. Abstract: Ensuring access to water, sanitation, and hygiene (WASH) for all requires a thorough understanding of the many contextual complexities that influence access to these services. Complexities spanning environmental, economic, political, and social dimensions, amongst others, can intersect and compound to hinder sustainable access to WASH for certain demographics or entire communities. This is of particular importance for challenging contexts where conventional WASH approaches are ineffective. Targeted approaches are required for these contexts to ensure that communities are not left behind in pursuit of the Sustainable Development Goals. Review of WASH literature identified seven broad types of challenging contexts: challenging environments, transient or environmentally-dependant communities, climate vulnerable communities, remote communities, poor urban communities, refugee camps, and emergency contexts. This review explores the intersecting complexities affecting access to WASH in these challenging contexts and how failure to understand the interconnectedness of these complexities has resulted in WASH solutions that are unaffordable, not inclusive, or unsustainable. To our knowledge, this review is the first of its kind. We emphasise the need to unpack intersecting complexities affecting WASH in challenging contexts, and we believe that incorporating such an approach early in WASH programs can ensure that intersecting complexities are accounted for in the design of WASH solutions. Ultimately, this novel lens may provide critical guidance for WASH programs in challenging contexts, ensuring that WASH solutions are contextually appropriate. Graphical abstract: Image, graphical abstract